CUSTOMER CAPITAL AS A KEY FACTOR OF E-COMMERCE MARKET DEVELOPMENT - Gottwald, Dalibor; Švadlenka, Libor; Pavlisová, Hana (My University, 2016)
The importance of customer satisfaction has always been crucial to development of every single market in general. E-commerce market has gained importance during the last few years – especially in terms of annual turnover of e-commerce market. This trend is the result of changes in customer behavior. Increasing customer loyalty is one of the keys to business success. Active customer policy is necessary for the development of the market in individual states. The central point of the issue is to find concrete social constructs which can explain customer behavior in recent years. The main objective of the research is to define the area of selected variables which can be regarded as crucial in the process of predicting development of e-commerce market. By using Theory of Planned Behavior (TPB), the dependence of development of e-commerce market on customer capital has been confirmed. Keywords: Communication, customer capital, e-commerce, B2C market.
Zákaznický kapitál jako klíčový faktor pro rozvoj e-commerce
Keywords: communication; customer capital; e-commerce; B2B market; spoje; zákaznický kapitál; e-commerce; trh B2B